Cyclopropene derivatives of aminosugars for metabolic glycoengineering - Hassenrück, Jessica; Wittmann, Valentin (Beilstein Journal of Organic Chemistry, 2019)
Cyclopropenes have been proven valuable chemical reporter groups for metabolic glycoengineering (MGE). They readily react with tetrazines in an inverse electron-demand Diels–Alder (DAinv) reaction, a prime example of a bioorthogonal ligation reaction, allowing their visualization in biological systems. Here, we present a comparative study of six cyclopropene-modified hexosamine derivatives and their suitability for MGE. Three mannosamine derivatives in which the cyclopropene moiety is attached to the sugar by either an amide or a carbamate linkage and that differ by the presence or absence of a stabilizing methyl group at the double bond have been examined. We determined their DAinv reaction kinetics and their labeling intensities after metabolic incorporation. To determine the efficiencies by which the derivatives are metabolized to sialic acids, we synthesized and investigated the corresponding cyclopropane derivatives because cyclopropenes are not stable under the analysis conditions. From these experiments, it became obvious that N-(cycloprop-2-en-1-ylcarbonyl)-modified (Cp-modified) mannosamine has the highest metabolic acceptance. However, carbamate-linked N-(2-methylcycloprop-2-en-1-ylmethyloxycarbonyl)-modified (Cyoc-modified) mannosamine despite its lower metabolic acceptance results in the same cell-surface labeling intensity due to its superior reactivity in the DAinv reaction. Based on the high incorporation efficiency of the Cp derivative we synthesized and investigated two new Cp-modified glucosamine and galactosamine derivatives. Both compounds lead to comparable, distinct cell-surface staining after MGE. We further found that the amide-linked Cp-modified glucosamine derivative but not the Cyoc-modified glucosamine is metabolically converted to the corresponding sialic acid.
Keywords: bioorthogonal chemistry; carbohydrates; cyclopropenes; inverse electron-demand Diels–Alder reaction; metabolic engineering

Essentials of Glycobiology - Varki, A.; Cummings, R. D.; Esko, J. D.; Freeze, H. H.; Stanley, P.; Bertozzi, C. R.; Hart, G. W.; Etzler, M. E. (Cold Spring Harbor Laboratory Press, 2009)

(untitled) - Laughlin, S. T.; Bertozzi, C. R. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Sminia, T. J.; Zuilhof, H.; Wennekes, T. (Carbohydr. Res., 2016)

(untitled) - Wratil, P. R.; Horstkorte, R.; Reutter, W. (Angew. Chem., Int. Ed., 2016)

(untitled) - Sletten, E. M.; Bertozzi, C. R. (Angew. Chem., Int. Ed., 2009)

(untitled) - Prescher, J. A.; Bertozzi, C. R. (Nat. Chem. Biol., 2005)

(untitled) - Kayser, H.; Zeitler, R.; Kannicht, C.; Grunow, D.; Nuck, R.; Reutter, W. (J. Biol. Chem., 1992)

(untitled) - Saxon, E.; Bertozzi, C. R. (Science, 2000)

(untitled) - Tornøe, C. W.; Christensen, C.; Meldal, M. (J. Org. Chem., 2002)

(untitled) - Rostovtsev, V. V.; Green, L. G.; Fokin, V. V.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2002)

(untitled) - Agard, N. J.; Prescher, J. A.; Bertozzi, C. R. (J. Am. Chem. Soc., 2004)

(untitled) - Ning, X.; Guo, J.; Wolfert, M. A.; Boons, G.-J. (Angew. Chem., Int. Ed., 2008)

(untitled) - Carboni, R. A.; Lindsey, R. V., Jr (J. Am. Chem. Soc., 1959)

(untitled) - Sauer, J.; Heldmann, D. K.; Hetzenegger, J.; Krauthan, J.; Sichert, H.; Schuster, J. (Eur. J. Org. Chem., 1998)

(untitled) - Braun, K.; Wiessler, M.; Ehemann, V.; Pipkorn, R.; Spring, H.; Debus, J.; Didinger, B.; Koch, M.; Muller, G.; Waldeck, W. (Drug Des., Dev. Ther., 2008)

(untitled) - Blackman, M. L.; Royzen, M.; Fox, J. M. (J. Am. Chem. Soc., 2008)

(untitled) - Devaraj, N. K.; Weissleder, R.; Hilderbrand, S. A. (Bioconjugate Chem., 2008)

(untitled) - Niederwieser, A.; Späte, A.-K.; Nguyen, L. D.; Jüngst, C.; Reutter, W.; Wittmann, V. (Angew. Chem., Int. Ed., 2013)

(untitled) - Späte, A.-K.; Schart, V. F.; Schöllkopf, S.; Niederwieser, A.; Wittmann, V. (Chem. – Eur. J., 2014)

(untitled) - Dold, J. E. G. A.; Pfotzer, J.; Späte, A.-K.; Wittmann, V. (ChemBioChem, 2017)

(untitled) - Späte, A.-K.; Dold, J. E. G. A.; Batroff, E.; Schart, V. F.; Wieland, D. E.; Baudendistel, O. R.; Wittmann, V. (ChemBioChem, 2016)

(untitled) - Patterson, D. M.; Nazarova, L. A.; Xie, B.; Kamber, D. N.; Prescher, J. A. (J. Am. Chem. Soc., 2012)

(untitled) - Cole, C. M.; Yang, J.; Šečkutė, J.; Devaraj, N. K. (ChemBioChem, 2013)

(untitled) - Späte, A.-K.; Bußkamp, H.; Niederwieser, A.; Schart, V. F.; Marx, A.; Wittmann, V. (Bioconjugate Chem., 2014)

(untitled) - Patterson, D. M.; Jones, K. A.; Prescher, J. A. (Mol. BioSyst., 2014)

(untitled) - Späte, A.-K.; Schart, V. F.; Häfner, J.; Niederwieser, A.; Mayer, T. U.; Wittmann, V. (Beilstein J. Org. Chem., 2014)

(untitled) - Xiong, D.-C.; Zhu, J.; Han, M.-J.; Luo, H.-X.; Wang, C.; Yu, Y.; Ye, Y.; Tai, G.; Ye, X.-S. (Org. Biomol. Chem., 2015)

(untitled) - Yang, J.; Šečkutė, J.; Cole, C. M.; Devaraj, N. K. (Angew. Chem., Int. Ed., 2012)

(untitled) - Hara, S.; Takemori, Y.; Yamaguchi, M.; Nakamura, M.; Ohkura, Y. (Anal. Biochem., 1987)

(untitled) - Nakamura, M.; Hara, S.; Yamaguchi, M.; Takemori, Y.; Ohkura, Y. (Chem. Pharm. Bull., 1987)

(untitled) - Hara, S.; Yamaguchi, M.; Takemori, Y.; Furuhata, K.; Ogura, H.; Nakamura, M. (Anal. Biochem., 1989)

(untitled) - Doll, F.; Buntz, A.; Späte, A.-K.; Schart, V. F.; Timper, A.; Schrimpf, W.; Hauck, C. R.; Zumbusch, A.; Wittmann, V. (Angew. Chem., Int. Ed., 2016)

(untitled) - Boyce, M.; Carrico, I. S.; Ganguli, A. S.; Yu, S.-H.; Hangauer, M. J.; Hubbard, S. C.; Kohler, J. J.; Bertozzi, C. R. (Proc. Natl. Acad. Sci. U. S. A., 2011)

(untitled) - Lin, W.; Gao, L.; Chen, X. (ChemBioChem, 2015)

(untitled) - Tan, H. Y.; Eskandari, R.; Shen, D.; Zhu, Y.; Liu, T.-W.; Willems, L. I.; Alteen, M. G.; Madden, Z.; Vocadlo, D. J. (J. Am. Chem. Soc., 2018)

(untitled) - Qin, W.; Qin, K.; Fan, X.; Peng, L.; Hong, W.; Zhu, Y.; Lv, P.; Du, Y.; Huang, R.; Han, M.; Cheng, B.; Liu, Y.; et al. (Angew. Chem., Int. Ed., 2018)

(untitled) - Luchansky, S. J.; Yarema, K. J.; Takahashi, S.; Bertozzi, C. R. (J. Biol. Chem., 2003)

(untitled) - Hinderlich, S.; Berger, M.; Schwarzkopf, M.; Effertz, K.; Reutter, W. (Eur. J. Biochem., 2000)